Relationship between Neutrophil-to-Lymphocyte Ratio and Liver Fibrosis in Nonalcoholic Fatty Liver Disease Among Adults in the United States: Data from the National Health and Nutrition Examination Survey 2017-2018 - Wang, Yuanyuan; Guo, Siqi; He, Yanfang; Zhang, Qiang; Zhou, Ni; Wang, Da; Mai, Ping (Turkish Journal of Gastroenterology, 2024)
Background/Aims: The relationship between neutrophil-to-lymphocyte ratio (NLR) and liver fibrosis in nonalcoholic fatty liver disease remains controversial. The aim of this study was to examine the association between NLR and liver fibrosis. Materials and Methods: We conducted a cross-sectional analysis using the National Health and Nutrition Examination Survey. Vibration-controlled transient elastography was used to assess liver fibrosis and its severity. Neutrophil-to-lymphocyte ratio was calculated as the ratio of neutrophil count to lymphocyte count. Results: This study included 1620 US adults with a mean age of 52.9 years, of which 53.3% were male. The obese population accounted for 62.5%, 68.5% had hypertension, 31.1% had diabetes, and 16% had significant liver fibrosis. After adjusting for all covariates, a positive correlation was observed between NLR and the severity of liver fibrosis (β = 0.57, 95% CI = 0.22-0.92, P = .001), which remained stable across different subgroups. Conclusion: This study suggests that elevated NLR levels are positively correlated with the severity of liver fibrosis in patients with nonalcoholic fatty liver disease, and these results can be well generalized to the US adult population. Cite this article as: Wang Y, Guo S, He Y, et al. Relationship between neutrophil-to-lymphocyte ratio and liver fibrosis in nonalcoholic fatty liver disease among adults in the United States: Data from the National Health and Nutrition Examination Survey 2017-2018. Turk J Gastroenterol. 2024;35(4):335-342.